Rainfall is not the most limiting factor to maize (Zea mays L.) production in intermediate rainfall regions of Zambia. Lessons from Choma District - Mubanga, Dr. Kabwe Harnadih; Steyn, Prof. Martin Joachim (Journal of Agricultural Policy, 2020)
Purpose: This study was based on the following objectives; (1) to investigate the sufficiency of rainfall received in Choma by assessing the differences in the precipitation received (PPT) against the potential evapotranspiration (PET) and actual evapotranspiration (ETa) for maize, and (2) to estimate potential for maize production in Choma under the current rainfall and temperature conditions. Methodology: The Soil Water Balance (SWB) crop growth model was used to analyze the rainfall-temperature interactions and estimate the maize stress index (SI) for analyses of crop water stress and potential yields (Yp). The relationships involving precipitation, potential and actual evapotranspiration were performed using time series auto regression and Fisher's least significant difference (LSD). Findings: Choma was not in a state of water deficit as maize water requirements were lower than precipitation. Maize water stress was destructive when it occurred in the mid than late stages of maize development. Mean precipitation (799.29mm) was higher than mean actual evapotranspiration (719.23 mm), though the difference was insignificant (F = 1.281; p = 0.126). However, potential evapotranspiration for maize in the area was significantly higher than the actual evapotranspiration (mean = 719.23) (F = 5.621; p = 0.012). Less destructive moderately dry periods seldom occurred during the sensitive initial and mid periods of maize development. Results: Farmers in Choma can potentially increase their rain-fed maize yields from the current 1.89 t/ha/year to 4.9 t/ha/year by managing limiting factors to maize production such as reduced access to fertilizer, declining of soil nutrients, late delivery of inputs, lack of markets, pests and lack of proper nutrient management. The study also showed that management rather than climatic conditions is responsible for the low yields in Choma area. Unique contribution to theory, practice and policy: The study established a methodology for simulating potential yields of farmers given existing climatic and soil conditions. Policy should concentrate on improving crop management rather than the current concentration on mitigating impacts of climate change as these are not the factors responsible for observed reduced crop yields.